Roles of Public Prosecutor's Office in Restorative Justice: A Focus on Prosecution Discontinuation Regulations - Sasongko, Andy (Universitas Serang Raya, 2023)
The implementation of restorative justice in criminal cases is crucial for upholding humanitarian values that prioritize the recovery and protection of both victims and offenders. This approach seeks to restore the situation to its original state without solely focusing on punishing the perpetrator, marking a paradigm shift towards reconciliation and healing. In Indonesia, restorative justice aligns with the societal need for more inclusive prosecutorial and judicial authority. Pre-court resolution of criminal cases must explore the potential for resolution before reaching a conviction. The Prosecutor's Office of the Republic of Indonesia holds a central role in executing this approach.The issuance of Prosecution Regulations Republic of Indonesia Number 15 of 2020, concerning the Termination of Prosecution Based on Restorative Justice, provides concrete guidance for the Attorney General of the Republic of Indonesia. This regulation emphasizes the recovery and protection of victims, aligning with broader aspects of humanity and justice. The primary objective is to establish public order, justice, truth, and legal certainty based on existing laws and values such as morality, religious norms, and courtesy. The Prosecution Regulations aims to encourage a more humane and conscientious approach by the Public Prosecutor, prioritizing the recovery of victims and the rehabilitation of offenders. This departure from traditional punitive thinking contributes positively to society. As an integral part of Indonesia's criminal justice system, the Prosecutor's Office bears significant responsibility in creating legal certainty, truth, legal order, and justice based on human values, morality, courtesy, and religious norms.This shift reflects a positive change in a criminal justice system that increasingly emphasizes inclusivity and social healing. Restorative justice goes beyond being a conceptual framework; it signifies a commitment to instigate positive transformations in the handling of criminal cases in Indonesia, ensuring that human values and justice form the bedrock of the justice system.